World - systems analysis and comparative education in the age of globalization - Arnove, Robert F. (Avances en Supervisión Educativa, 2010)
This article explores the application of world-systems analysis (WSA) to the comparative study of education systems. Two main theoretical approaches to the study of transnational trends in education are identified: namely political realist and neoinstitutionalist. Following a discussion of their intellectual origins and basic assumptions, the article turns to an analysis of the articulation of world-systems analysis with the growing body of globalization research. The interactions between global economic and cultural forces and local contexts are illustrated in representative case studies in the field of comparative and international education. Special attention is given to the impact of major international governmental agencies as well as nongovernmental organizations on education policy agencies. Advances in telecommunication technologies, which compress time and space, are then analyzed with regard to how they shape the nature of work and education system responses. A penultimate section contrasts "globalization from above" with "globalization from below," the cross-national linking protest movements aimed at achieving more equitable education systems and just societies. The concluding section summarizes how different approaches to worldsystems analysis, within the more general framework of globalization research, can contribute to theory -building and more enlightened educational policy and practice- principal goals of the field of comparative and international education.